Respuestas
Respuesta dada por:
5
por la condición del problema tenemos
![x + y = 12 ....(1) \\ x - y = - 6.....(2) x + y = 12 ....(1) \\ x - y = - 6.....(2)](https://tex.z-dn.net/?f=x+%2B+y+%3D+12+....%281%29+%5C%5C+x+-+y+%3D++-+6.....%282%29)
si se suma (1) +(2)
![2x = 6 \\ x = 3 2x = 6 \\ x = 3](https://tex.z-dn.net/?f=2x+%3D+6+%5C%5C+x+%3D+3)
reemplazando el valor de x en (1)
![3 + y = 12 \\ y = 9 3 + y = 12 \\ y = 9](https://tex.z-dn.net/?f=3+%2B+y+%3D+12+%5C%5C+y+%3D+9)
los dos números son:
![x = 3 \\ y = 9 x = 3 \\ y = 9](https://tex.z-dn.net/?f=x+%3D+3+%5C%5C+y+%3D+9)
si se suma (1) +(2)
reemplazando el valor de x en (1)
los dos números son:
Preguntas similares
hace 6 años
hace 9 años